2010
DOI: 10.1007/s10517-010-0873-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-kB, p53, and p21 in the Regulation of TNF-α Mediated Apoptosis of Lymphocytes

Abstract: The effect of recombinant TNF-α on programmed death of donor lymphocytes was studied in vitro. The proapoptotic effect of this cytokine is realized through transcription factors and cell cycle inhibitors. Incubation of lymphocytes with recombinant TNF-α revealed increased levels of NF-kB and p21 and reducted content of nonphosphorylated p53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…For diVerent types of cells and in response to diVerent stimuli, p53 is regulated by transcription factors, such as NF-B, AP-1, and STAT (Ho and Ames 2002;Ryazantseva et al 2010). In a previous study, we found a signal pathway that inhibits p53 function through NF-B/mot-2 in HELF cells .…”
Section: Discussionmentioning
confidence: 84%
“…For diVerent types of cells and in response to diVerent stimuli, p53 is regulated by transcription factors, such as NF-B, AP-1, and STAT (Ho and Ames 2002;Ryazantseva et al 2010). In a previous study, we found a signal pathway that inhibits p53 function through NF-B/mot-2 in HELF cells .…”
Section: Discussionmentioning
confidence: 84%
“…These complexes block the cell-cycle transition from the G1 phase to the S phase. P21 is regulated by two different pathways, i.e., a p53-dependent pathway (DNA damage leading to the activation of p53 and upregulation of p21 causing cell cycle blockage in the G1 phase with possible DNA repair or induction of apoptosis), and a p53-independent pathway (through cell growth factors, such as interferon-β and tumor necrosis factor-α, which are able to induce p21 in p53-deficient cells in quiescence) [ 25 , 26 ]. Our results also indicated that p21 overexpression was connected with the depression of CDK 2 and cyclinE in human RPE cells, leading to arrest of the cell cycle and reduction of the proliferation of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen activation of human primary lymphocytes in vitro results in an increase in both TNF and CDKN1A mRNA levels, whereas treatment with the immunosuppressant cyclosporin, which inhibits T lymphocyte proliferation, reduces TNF mRNA levels but increases expression of CDKN1A both at the level of mRNA and protein (Khanna 2005). Treatment of human PBMC with TNF in vitro increases apoptosis and necrosis via a process that involves increases in levels of CDKN1A protein (Ryazantseva et al 2010). TNF has also been shown to stimulate CDKN1A expression, both at the level of mRNA and protein in murine alveolar cells and macrophages, while CDKN1A can suppress TGF-b induced TNF expression (Yamasaki et al 2008).…”
Section: Effects Of Extended Fast On Pbmc Transcription Profilesmentioning
confidence: 99%